Location Is Everything: An Educational Primer for Use with "Genetic Analysis of the Ribosome Biogenesis Factor Ltv1 of Saccharomyces cerevisiae". Issue 2 (2nd February 2015) - Edwalds-Gilbert, Gretchen
Abstract: The article by Merwin et al. in the November 2014 issue of GENETICS provides insight into ribosome biogenesis, an essential multistep process that involves myriad factors and three cellular compartments. The specific protein of interest in this study is l ow-t emperature v iability protein (Ltv1 ), which functions as a small ribosomal subunit maturation factor. The authors investigated its possible additional function in small-subunit nuclear export. This Primer provides information for students to help them analyze the paper by Merwin et al. (2014), including an overview of the authors' research question and methods. Related article in GENETICS : Merwin, J. R., L. B. Bogar, S. B. Poggi, R. M. Fitch, A. W. Johnson, and D. E. Lycan, 2014 Genetic analysis of the ribosome biogenesis factor Ltv1 of Saccharomyces cerevisiae . Genetics 198: 1071–1085